STUDI FENOMENOLOGI: PENGALAMAN KONTROL DIRI KLIEN INTERVENSI BERBASIS MASYARAKAT (IBM) DALAM PENYALAHGUNAAN NARKOBA - Lusiana, Sambrina Aulia; Fitriana, Siti; Dhyah Yulianti, Padmi (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2026)
Drug abuse is a complex issue that involves not only medical aspects but also requires self-control skills so that individuals can maintain the recovery process and prevent relapse. This study aims to explore in depth the self-control experiences of Community-Based Intervention (IBM) Mekar Berseri clients involved in drug abuse, focusing on behavioral control, cognitive control, and decision-making control during the rehabilitation period. This study uses a qualitative approach with a phenomenological design to explore the clients' subjective experiences from their own perspectives. The study participants were three IBM clients selected using a purposive sampling technique in accordance with the research criteria. Data collection was conducted through semi-structured interviews to obtain in-depth data. Data analysis was conducted using Interpretative Phenomenological Analysis (IPA) with the help of NVivo software. The results showed that clients' self-control developed in three main aspects. In the behavioral control aspect, clients were able to divert themselves to positive activities, avoid triggering situations, and refuse risky invitations. In the cognitive control aspect, clients were able to calm their minds, maintain a positive mindset, and think before acting. Meanwhile, in terms of decision-making control, clients were able to consider the consequences of their actions, choose more adaptive decisions, and link life choices to long-term recovery goals. These findings indicate that IBM plays a crucial role as a community based rehabilitation method in continuously strengthening clients' self-control.upports the ongoing strengthening of clients' self-control